GET VALUABLE INFORMATION FROM THE DATA GRAVEYARD - Bauer, M. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Continuous measurements such as temperature, pressure, or flow are recorded and stored in the plant data history of industrial chemical plants. Frequently, data is accumulated and kept in storage without anyone drawing further conclusions from it about the state of the process. This paper shows how historical data can give insight into the operation of a chemical plant. The time and frequency analysis methods are explained via an industrial process at Eastman Chemical Company, Tennessee. A procedure for systematic data analysis is given. Combined with expert knowledge of the process, causes of disturbances affecting the process can be identified. AFRIKAANSE OPSOMMING: Kontinue meting van veranderlikes soos temperatuur, druk en vloei word aangeteken en bewaar as